Circ_KATNAL1 promotes the inflammation and apoptosis in human middle ear epithelial cells induced by lipopolysaccharide by regulating the miR-153-3p / TLR4 axis: Circ_KATNAL1 promotes the inflammation and apoptosis - Guo, Siquan; Qin, Feng; Wang, Jiang; Ding, Yongqing; Xue, Haixiang; You, Jianqiang; Chao, Changjiang (Cellular and Molecular Biology, 2023)
The purpose of this experiment was to explore the effects and mechanism of circ_KATNAL1 on inflammatory injury and apoptosis of human middle ear epithelial cells (HMEECs) induced by lipopolysaccharide (LPS). For this aim, the cell inflammatory injury model was established by HMEECs cells induced by LPS. It was divided into a blank control, model, circ_KATNAL1 and circ_KATNAL1 + LPS groups. The cell viability was detected by the MTT method. The apoptosis rate of each group was detected by flow cytometry. The cell migration ability of each group was detected by cell scratch assay. The mRNA expression levels of miR-153-3p and TLR4 in the cells of each group were detected by RT -PCR method. The protein expressions of BCL-2 and TLR4 in the cells of each group were detected by WB method. The levels of IL-6 and TNF-α were detected by ELISA method. Results showed that compared with the control group, the cell viability in the model group was decreased, the cell apoptosis rate was increased, the cell migration ability was weakened, the mRNA expression level of miR-153-3p and protein expression level of BCL-2 in the cells were decreased, and the mRNA and protein expression levels of TLR4 were increased and the levels of IL-6 and TNF-α in the cell supernatant were increased. Compared with the model group, the cell viability in the circ_KATNAL1 group was increased, the cell apoptosis rate was decreased, and the cell migration ability was increased, the mRNA expression level of miR-153-3p and BCL-2 protein expression level in the cells were increased, the mRNA and protein expression levels of TLR4 were decreased, and the contents of IL-6 and TNF-α in the cell supernatant were decreased. Compared with the model group, the cell viability in the circ_KATNAL1 + LPS group was decreased, cell apoptosis rate was increased, cell migration ability was weakened, the mRNA expression level of miR-153-3p and protein expression level of BCL-2 in cells were decreased, mRNA and protein expression levels of TLR4 were increased, and the content of IL-6 and TNF-α in the cell supernatant were increased. The differences were all statistically significant (P ﹤0.05). It showed that LPS could promote cell injury by increasing inflammatory cell pyroptosis, and the abnormal expression of circ_KATNAL1 played an important role in cell inflammation induced by LPS. Up-regulation of circ_KATNAL1 could promote inflammatory pyroptosis in HMEECs induced by LPS. miR-153-5p and TLR4 were downstream targets of circ_KATNAL1. The inhibition of miR- 153-5p or up-regulation of TLR4 could reverse the protective effects of silencing circ_KATNAL1. In conclusion, circ_KATNAL1 can promote an inflammatory role in human middle ear epithelial cells through the miR- 31-5p / TLR4 axis, which may become an important target for the diagnosis and treatment of otitis media.